Effects of Maxillary Expansion on Mastication and Muscle Activity: Case Series - Alves Valentim da Silva, Livia Maria (2026)
This case series evaluated three children with maxillary transverse deficiency and a habitual unilateral mastication preference who were treated with rapid maxillary expansion (RME). Considering the growing recognition of functional alterations in children with transverse deficiencies, RME has been proposed as a therapeutic approach capable of remodeling skeletal structures and influencing muscular dynamics. Electromyographic activity of the bilateral masseter, temporalis, and upper and lower orbicularis oris muscles was recorded during rest, dental clenching, suction, swallowing, and non-habitual mastication at baseline (T0), six months (T1), and eighteen months (T2). By six months, transverse deficiencies were corrected in all patients, with increases in anterior and posterior arch widths and closure of the anterior open bite, and these skeletal and dental changes remained stable throughout the 18-month follow-up. Functionally, an initial increase in orbicularis oris activity and improved muscular symmetry were observed at six months; partial asymmetry reappeared at 18 months, reflecting the persistence of habitual right-sided unilateral mastication. RME produced stable skeletal and dental outcomes and promoted early functional adaptations in these three patients, but when used in isolation, it was insufficient to induce lasting modifications of their established unilateral masticatory patterns, highlighting the need for multidisciplinary management to achieve long-term functional stability.